Sĕkar Cina Gambuh: Anomali Metrum Gambuh pada Teks Swara Sĕstra - Wijanarko, Fajar (Balai Bahasa Jawa Barat, 2018)
The writing of sastra kapujanggan (poetry literature) is always used the meter as rule should be obeyed. However, the study of meter as the rules poetry is rarely found. If we are given the necessary attention, there are many meters that have not been identified or it lost along with the loss of literature. The main aim of this research is to reveal the Cina Gambuh meter in the text of Swara Sĕstra as an anomaly meter of Gambuh song pattern. This study is done by focusing on discipline of philology and codicology as the method. While, the method of codicology is done by comparing an alphabet pattern of the Swara Sestra with another text from Pakualaman's scriptorium in a similar script style to identify the text. The other aim of this study is to identify another variety meter and add the list meter of Gambuh. At the end of the study, the anomaly song pattern of Gambuh, in fact, is a creativity of the writer Jayengminarsa from Pakualaman.